Knowledge, attitudes, and behavior of Health Sciences students toward organ donation/ Suzana Yusof, Haikal Khalidah Khalid and Nur Atira Husna Sukimi - Yusof, Suzana; Khalid, Haikal Khalidah; Sukimi, Nur Atira Husna (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Organ donation rates decrease in need worldwide. Malaysia also suffers from a chronic shortage of organs for transplantation. Health Sciences Students are future health care professionals which to raise the donation rates, their knowledge, attitude, and behavior toward organ donation are crucial. The aim of this study is to identify the level of knowledge, attitudes, and behavior of Health Sciences Students in UiTM Puncak Alam toward organ donation. This is a cross-sectional study design. Using a convenience sampling and modified self-administered questionnaire from a total of 312 respondents in UiTM Puncak Alam. Majority respondents (53.5%, n=167) had good knowledge, and all (100%, n=312) are aware of organ donation. However, only less than half of the participants (45.8%, n=143) showed a positive attitude toward organ donation. 128(41%) of respondents have favorable behavior toward organ donation. Results from correlation revealed that having good knowledge does not correlate to either positive attitudes or favorable behavior; however, positive attitudes had shown correlated to favorable behavior toward organ donation. The study revealed that the attitudes and behavior of the respondents toward organ donation are not proportional to the level of knowledge they possess. Therefore, better educational plans on organ donation among students are needed.